Needs Analysis for Designing English Course for Tourist Police in Mandalika Special Economic Zone - Ingtias, Lalu Lumebet; Sujana, I Made; Susanti, Ni Wayan Mira; Kamaludin, Kamaludin (Jurnal Ilmiah Profesi Pendidikan, 2024)
In the era of globalization and increasing international travel, effective communication in English has become a fundamental requirement for individuals working in various professional fields.The objectives of this research are to find out the authentic tasks and authentic texts that needed to be included in designing English for the tourist police in Mandalika Special Economic Zone (Mandalika SEZ), and to know how the design of the English course for tourist police in Mandalika Special Economic Zone (Mandalika SEZ) to improve language skills in their workplace. The subjects of the study are five tourist police officers who are fluent in English from 15 Tourist Police officers who work in the Mandalika Economic Zone. The techniques used to collect the data are observation, interview, questionnaire, and focus group discussion. The data analysis technique follows Miles and Huberman’s model (reduction, data display, conclusion drawing/verification, and syllabus design). The syllabus encompasses a total of seven key authentic tasks tailored to enhance the officers' communication and operational capabilities in various scenarios. These tasks include: Communicating During Emergencies, Giving Directions, Conducting Safety Checks, Conflict Resolution, Writing Reports, and Providing Assistance. In conclusion, the English syllabus for tourist police officers in Mandalika SEZ is carefully crafted to meet their needs through practical tasks, relevant materials, and effective assessment methods. This design enhances both language skills and real-life problem-solving abilities, serving as a valuable model for future training and improving the overall service quality and efficiency of the officers.